FENOMENA CAMPUR CODE PADA POSTINGAN @Zil_hb 2021-2025. - Nosi Vellila; Leli Nisfi Setiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the phenomenon of code-switching in Instagram posts by @Zil_hb during the period 2021–2025. The method used is qualitative descriptive using documentation techniques. The results of the study show that the code-switching found consists of internal and external code-switching. The majority consists of external code-switching compared to internal code-switching. Internal code-switching includes the use of regional languages, while external code-switching includes foreign languages, particularly English. Factors influencing the use of this phenomenon include communication style, social identity, and the influence of globalization.